PEMELIHARAAN IKAN GABUS (Channa striata) DENGAN PADAT TEBAR BERBEDA DALAM MEDIA BIOFLOK - ade dwi sasanti; yulisman . (Jurnal Akuakultur Rawa Indonesia, 2016)
ABSTRACT Increasing density in fish culture is one of the effort to increase fish culture production. The aim of the research was to determine the best stocking density of snakehead that reared in biofloc media. The research conducted on July-August 2015 in Laboratorium Budidaya Perairan, Aquaculture Study Program, Agriculture Faculty, Sriwijaya University. The research based on completely randomized design with three treatments and three replications. The treatments were 150 fish.m-3 (P1), 300 fish.m-3 (P2) and 450 fish.m-3 (P3). The research parameters were survival rate, absolute length and weight growth, feed efficiency, floc volume, total of lactic acid bacteria and water quality. The best density of this research was treatment P1 which density of 150 ind.m-3 with survival was 98.52%, absolute lenght growth was 2.18 cm, absolute weight growth was 7.85 g and feed efficiency was 90.73%. Â  Key words : Biofloc, Snakehead fish, Stocking density